A bibliometric analysis of research on craniomaxillofacial distraction osteogenesis from 2000 to 2021 - Liu, Zhen; Yang, Jianying; Zhou, Changhan; Liu, Yao; Luo, En (Frontiers in Surgery, 2022)
Objective This study collected and summarized publications related to craniomaxillofacial distraction osteogenesis(DO) from 2000 to 2021, investigated trends in related research, and compared publications from different countries, institutions and journals. The aim is showcasing hotspots and frontiers in tensor fasciae research and providing a reference for future research. Background Craniomaxillofacial DO serves to treat different types of craniomaxillofacial dysplasia and bone defects and deformities. DO can significantly reduce surgical trauma, complications, and recurrence rate compared to conventional surgery. However, there is a lack of bibliometric analyses regarding Craniomaxillofacial DO. Methods CiteSpace and VOSviewer were used to analyze and visualize 3141 articles and reviews searching through the Web of Science Core Collection(WOSCC) to obtain publications on craniomaxillofacial DO from 1 Jan 2000 to 31 Dec 2021. Results In the last 21 years, there has been a significant increase in the number of publications. The United States, the People's Republic of China, and Italy produce the vast majority of publications. University of Milan and University of Bologna are the most influential in this field. McCarthy JG and Ilizarov GA are the most influential authors. Obstructive sleep apnea, TMJ ankylosis and cleft lip and palate are potential research direction in this field. Conclusion Future research should focus on the precise indications and optimal timing of craniomaxillofacial DO and the evaluation of the long-term outcomes of various modified procedures. This study provides a relatively objective reference for related researchers, medical practitioners, and global health systems.